Impact of knowledge management capabilities on new product development performance through mediating role of organizational agility and moderating role of business model innovation - Idrees, Hisham; Hynek, Josef; Xu, Jin; Akbar, Ahsan; Jabeen, Samrena (Frontiers in Psychology, 2022)
In several studies, knowledge is witnessed as one of the foundations of long-term competitive edge and is also a basic source of new product development (NDP) performance. The aim of this study is to investigate the role of knowledge management capabilities (KMC) in new product development performance with the mediating role of organizational agility. Additionally, this study also intends to examine the moderating role of business model innovation on the relationship of KMC with organizational agility. This study was conducted on the Chinese automobile sector, and the NPD project managers, supervisors, and engineers of the sector were respondents of this study. A survey questionnaire was used to collect the data from 201 respondents, and data were analyzed using the Smart PLS 3 software. The findings of this research, although limited to the automobile industries, indicate that knowledge sharing and knowledge application have significant and positive effects on the development of new products. Organizational agility significantly mediates the relationship of KMC with NPD. The results found that business model innovation has a significant moderating role in the relationship between KMC and organizational agility. Moreover, the results of this study will assist the managers in developing a modern competitive business environment by implicating KMC in the process of NPD. Lastly, organizations may improve the sustainability of their product and their overall performance by using organizational agility and modern ways of value delivery.